Predicting Teacherpreneurial Competencies based on their mindset, mutual trust, organization culture and connections - Mulyani, Endang; Susilowati, Nenden; Alwi, Ahmad; Prilanita, Yeni; Suyanto, Umar (Technium Social Sciences Journal, 2025)
The current economic turmoil demands changes to the spectrum of education. It is evident that the disruption of the labor market is difficult for the world of education to meet. Even the economic turmoil that occurs also affects the needs of educators and education personnel. Education personnel who have leadership skills are only suitable for the past era, but along with the development of the discourse that teachers must also become teacherpreneurs in the future This research seeks to construct indicators of teacherpreneur, identify factors that influence it and see how much influence it has. This research will use a quantitative approach with EFA and CFA methods using the SmartPLS tool. The results of the study have four findings, the first relationship between Mutual Trust and Teacherprenuer description that The coefficient of 0.102 indicates a significant, albeit relatively small, positive relationship between Mutual Trust and Teacherprenuer. That is, the higher the level of Mutual Trust in the educational environment, the higher the likelihood of an increase in Teacherprenuere. The Second relationship between connection and Teacherprenuer the coefficient of 0.116 shows a slightly larger positive relationship compared to Mutual Trust. This means that the stronger the Connection (i.e. good social or professional relationships between teachers, colleagues and institutions), the higher the likelihood of Teacherprenuere. The Third relationship between Growth Mindset and Teacherprenuer, the coefficient of 0.295 shows a greater influence, meaning that Growth Mindset (the belief that abilities can develop through effort and learning) has a stronger influence on Teacherprenuere than Mutual Trust and Connection.Growth Mindset plays an important role in encouraging teachers to continue to develop and persist in their profession. The Last relationship between Culture and Teacherprenuer The coefficient of 0.169 indicates a significant positive relationship between Culture (a supportive organizational culture in the workplace) and Teacherprenure. A supportive, inclusive and collaborative culture in a school or educational institution can influence teachers to stay longer in the profession.